Significantly enhanced mid Holocene fluvial activity in a globally important, arid‐zone wetland: The Okavango Delta, Botswana. Issue 3 (6th January 2022) - Tooth, Stephen; McCarthy, Terence S.; Duller, Geoff A. T.; Assine, Mario L.; Wolski, Piotr; Coetzee, Grace
Abstract: Information on past dryland environments is commonly derived from geomorphological landforms and sediments ('geoproxies'). The Okavango Delta in the middle Kalahari, Botswana, has been subject to a long history of arid–humid transitions but its potentially rich archive of fluvial geoproxies is largely untapped. Previous palaeoenvironmental studies in the Delta region have focused mainly on aeolian dunes, lacustrine beach ridges, and rare pollen sequences in surrounding locations, and the Delta's channel dynamics have remained poorly constrained, both chronologically and in quantitative palaeohydrological terms. Focusing on the Delta's Xugana region, we present the first optically stimulated luminescence ages for palaeochannel fills and scroll bars, revealing significantly enhanced fluvial activity in the ~7–4 ka interval. Along 120–150 m‐wide, sand‐bed, sinuous palaeochannels, lateral migration and bend cutoffs were driven by palaeodischarges up to ~350–450 m 3  s −1, at least nine times those of the present‐day channels. These palaeochannels represent the last major phase of meander activity in the middle and lower Delta. The palaeodischarges imply significantly higher rainfall over the catchment in the mid Holocene, possibly resulting from a southwards shift of the African tropical rainbelt. Over the last few thousand years, diminished fluvial activity in the Xugana region has continued; <20 m‐wide channels with discharges typically <40 m 3  s −1 have been more laterally stable, albeit subject to local avulsions. These findings provide the 'missing link' between evidence for past intervals of enhanced rainfall in the Delta's tributary catchments in the northwest and west and the filling of large lacustrine basins to the southeast and east. The findings contribute to improved understanding of changing Kalahari hydroclimates and support growing evidence indicating that the mid to late Holocene was a time of significant fluvial transformation across many of the world's drylands. Abstract : luminescence ages for palaeochannels in the Xugana region of the Okavango Delta, Botswana, reveal significantly enhanced mid Holocene (~7‐4 ka) fluvial activity lateral migration in wide palaeochannels was driven by discharges at least nine times that of present‐day channels, as controlled by southwards shift of rainfall belts the findings contribute to emerging understanding of changing late Quaternary hydroclimates in the Kalahari, and to growing evidence for mid‐late Holocene river transformations in many drylands worldwide